Adapting to Disruptive Changes in the Digital World: Management Consulting Majors - Alexey Bereznoy (Foresight and STI Governance)
Management consulting is one of the most dynamically growing sectors of the modern global economy, characterized by a very high resilience to the fluctuations of the macroeconomic environment. Nevertheless, a number of prominent researchers note the disruptive trends in the global consulting industry and predict the disruptive effects of the realization of these trends for the traditional leaders of the consulting business due to the spread of digital technologies, especially big data analytics and artificial intelligence. In an effort to understand the validity of such assessments, the author of this article consistently analyzes the features of the evolution of the management consulting industry landscape, examines the key factors of disruptive changes that deepening digitalization brings to the consulting industry, and considers the main mechanisms used by global industry leaders to adapt to the rapidly evolving digital environment. It is concluded that, despite the challenges of the digital transformation, these leaders not only continue to grow dynamically, maintaining their dominant positions on global markets, but are also very active in penetrating new market segments emerging in the face of digital shifts.